SPE/IATMI Asia Pacific Oil &Amp; Gas Conference and Exhibition 2015
DOI: 10.2118/176410-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Correlation to Predict the SAGD Recovery Performance

Abstract: The prediction of the recovery performance for Steam-Assisted-Gravity-Drainage (SAGD) process is becoming increasingly important as the SAGD projects all over the world continue to increase. The prediction of SAGD recovery performance should go back to the theory basis developed by Butler (1978). Afterwards, based on his model, many modified models are proposed. But most of these models are analytical or semi-analytical methods, and the predicting process is much complicated. In particular for the SAGD project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…The different timescale data were selected to train the machine learning models. The numerical results confirmed the superiority of the SGB model in predicting the oil recovery factor. , , …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The different timescale data were selected to train the machine learning models. The numerical results confirmed the superiority of the SGB model in predicting the oil recovery factor. , , …”
Section: Introductionsupporting
confidence: 55%
“…The numerical results confirmed the superiority of the SGB model in predicting the oil recovery factor. 5 , 7 10 , 12 15 …”
Section: Introductionmentioning
confidence: 99%
“…Through literature review and field experience, a series of typical attributes which could be considered in the numerical simulation model are chosen as input parameters. 30 34 Input parameters attached to initial conditions include initial reservoir pressure, initial oil saturation, and thermal conductivity of rocks. Input parameters attached to reservoir characteristics include effective thickness, porosity, horizontal permeability, and ratio of vertical permeability to horizontal permeability.…”
Section: Methodsmentioning
confidence: 99%
“…Siavashi et al used a numerical simulation to analyze the influence of steam injection temperature, well rates, and different distances between injection-production wells (9,14,20, and 27 m) on oil recovery in SAGD process; the result showed that the steam temperature and well distance remarkably had an effect on SAGD performance; the oil production increased with well distance widening [29]. Dong et al developed sensitivity analysis model to comprehensively evaluate the influences of reservoir/fluid parameters and operation parameters on SAGD recovery performance, which confirmed that reservoir thickness, permeability, and pressure have great influence on SAGD production [30]. Zhang et al used a 2D numerical model to predict the lateral spreading and confinement stage of steam chamber, and they also found that a higher steam pressure results in a higher oil rate [31].…”
Section: Introductionmentioning
confidence: 99%